Regulation of socio-environmental risks in southern Chile: analysis of responsible pet ownership and urban pollution from domestic firewood use - Sáez Ardura, Felipe; Vallejos Romero, Arturo; Boso Gaspar, Àlex; Ortiz Noguera, Guadalupe; Cordoves-Sánchez , Minerva; Cisternas Irarrázabal , César; Rodríguez Rodríguez , Ignacio; Arias Lagos , Loreto (Revista del CLAD Reforma y Democracia, 2024)
Using the Risk Regulation Approach, we analyze two socioenvironmental risk regimes in La Araucanía, Chile. Applying a qualitative methodology, we characterize the regulatory configuration of pet ownership and urban pollution by using firewood at the regional scale. Our findings show regulatory differences between the regimes, with more significant regulatory development and efficiency in the latter than in the former. Thus, in Chile, regulatory efforts are being deployed with greater intensity to address the risk of exposure to an externality generated by economic and productive reasons rather than those caused by socio-cultural reasons, as in the case of pets. Although there are regulatory advances in both areas, there are also marked shortcomings in the institutional attention given to these socio-environmental problems. These results can be illustrative for understanding other areas of socio-environmental risk management in different Latin American countries, assuming risk policies are infrequent in the region.
Keywords: Risk Regulation Approach; socio-environmental risks; pets; contamination from firewood use; Chile